Effect of dietary natural supplements on immune response and mineral bioavailability in piglets after weaning - I. Taranu; D.E. Marin; A. Untea; P. Janczyk; M. Motiu; R.D. Criste; W.B. Souffrant (Czech Journal of Animal Science, 2012)
Plants and plant extracts (PPEs) have gained increasing interest as feed additives and possible replacing antibiotics for pig productions. The effects of dietary Chlorella vulgaris (1%), sodium alginate (0.1%), inulin (1.5%), and a mixture of essential oils (0.04%) supplements on immune response, and bioavailability of some micronutrients (iron - Fe, copper - Cu, manganese - Mn, and zinc - Zn) were investigated in weaned piglets in this study. The results showed that the concentration of IgG was increased in the plasma of pigs fed the PPEs supplemented diets being significantly higher (P < 0.05) in the case of dietary sodium alginate supplementation in comparison to the control (6.00 vs. 4.03 mg/ml). In liver, PPEs, especially inulin and essential oils, were able to modulate the level of cytokine production and mineral retention, resulting in higher liver concentration of IL-1β (125.4 and 88.9%), IL-8 (136.9 and 61.3%), TNF-a (296.6 and 121.6%), and IFN-γ (51.2 and 107.28%), Cu (71.31 ppm), and Fe (192.56 ppm) in comparison to the control. The results of this experiment indicate that natural supplements investigated herein, especially inulin, essential oils, and sodium alginate had the ability to potentiate both the immune function and mineral retention during the initial post weaning period.